Relationship between stress hyperglycemia ratio of one-year mortality in patients with heart failure: Analysis of the MIMIC-IV database. - Yimeng Wang; Wei Xu; Jingyang Wang; Yuyuan Shu; Yinjing Xin; Yanmin Yang (PLoS ONE)
Background Stress Hyperglycemia Ratio (SHR) has been confirmed to be a predictor for adverse outcomes in cardiovascular diseases in recent years. However, the impact of SHR on one-year mortality in patients diagnosed with heart failure (HF) is still unclear. This study aims to explore the relationship between SHR and one-year mortality in HF patients, both complicated with and without diabetes mellitus (DM). Methods This study enrolled 3747 patients with HF from the Medical Information Mart for Intensive Care (MIMIC-IV) database. 1865 patients were set into the group of lower SHR (SHR < 0.964) and 1882 patients were in the higher group (SHR ≥ 0.964). The primary endpoint was one-year mortality. Results The mean age of the total study population was 69 ± 13, and 1530 (40.8%) of them were female. Finally, 188 (5.0%) patients died in the hospital and 766 (20.4%) patients died during a one-year follow-up. Patients in the higher SHR group had a longer hospital stay (2.7% vs. 2.4%, p < 0.001) and higher in-hospital mortality (8 vs. 7, p < 0.001) than those in the lower group. The Kaplan-Meier curves also show that higher SHR is associated with an elevated risk of one-year mortality in patients with HF, both in the DM and non-DM groups (all log-rank p < 0.0001). As a continuous variable, SHR was an independent predictor for one-year mortality [hazard ratio (HR), 2.893; 95% confidence interval (CI), 2.198-3.808]. Elevated SHR was significantly associated with higher risk of one-year mortality in patients with (HR, 1.499; 95% CI, 1.104-2.036) and without DM (HR, 1.300; 95% CI, 1.096-1.542), consistently. The RCS curve shows a gradual increase in the probability of one-year mortality as the value of SHR increases for HF patients. Conclusion Our findings indicated that a higher level of SHR was associated with elevated one-year mortality in HF patients both with and without DM, suggesting that SHR is a promising stratification indicator for predicting the risk of death in patients with HF.